2022
DOI: 10.1002/jhet.4460
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of novel 2‐arylquinoline‐3‐fused thiazolo[2,3‐c]1,2,4‐triazole heterocycles as potential antiproliferative and antimicrobial agents

Abstract: A series of novel 2-arylquinoline-3-fused thiazolo[2,3-c]1,2,4-triazole heterocycles 9a-t were efficiently synthesized using simple conventional methods in good yields. The structure of newly synthesized molecules was characterized on the basis of their IR, 1 H NMR, 13 C NMR and mass spectral data. Among 9at, compounds 9h, 9n, 9b and 9d exhibited highly significant antiproliferative activity against two cancer cell lines C6 (nerve cells) and MCF-7 (human breast adenocarcinoma cells) when compared with standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…This is evi-denced by the use of drugs Itraconazole, Fluconazole in the world medical practice. The works of scientists [11][12][13][14][15][16][17][18][19][20] confirm this. Systematizing the literature, we can conclude that the substituents adamantane, 5-amino-2-hydroxybenzoate, 4-fluoro-2-phenoxyphenyl, 2-bromophenyl and hydroxybenzylidene fragment in the 5 position of the heterocyclic system of 1,2,4-triazole lead to an increase in antifungal action.…”
Section: Antifungal Activity Of 124-triazole Derivativesmentioning
confidence: 74%
See 1 more Smart Citation
“…This is evi-denced by the use of drugs Itraconazole, Fluconazole in the world medical practice. The works of scientists [11][12][13][14][15][16][17][18][19][20] confirm this. Systematizing the literature, we can conclude that the substituents adamantane, 5-amino-2-hydroxybenzoate, 4-fluoro-2-phenoxyphenyl, 2-bromophenyl and hydroxybenzylidene fragment in the 5 position of the heterocyclic system of 1,2,4-triazole lead to an increase in antifungal action.…”
Section: Antifungal Activity Of 124-triazole Derivativesmentioning
confidence: 74%
“…1). The results considered in [11][12][13][14][15][16][17][18][19] indicate inhibition P. cubensis, A. niger, S. fuligenea, F. oxysporum, X. Axonopodis, C. cassiicola and other strains of pathogenic fungi.…”
Section: Antifungal Activity Of 124-triazole Derivativesmentioning
confidence: 99%
“…These results align with previously published studies that have reported on the antibacterial and antifungal properties of similar compounds. 39 Based on the obtained results, it is evident that the synthesized triazole derivatives have the potential to serve as valuable agents for the design and development of novel therapeutic drugs to combat bacterial resistance.…”
mentioning
confidence: 92%
“…The 1,2,4-triazoles derivatives have been found to possess wide spectrum of biological activities [30][31][32][33]. Numerous triazole-based drugs has been developed as antibacterial [34], antifungal [35], anti-malarial [36], anticancer [37], antidiabetic [38].…”
Section: Introductionmentioning
confidence: 99%